Evidence for an increase of DNA contour length at low ionic strength. - Geller, K (1980)
The polyion chain expansion of DNA was studied by viscometry within the Na+ concentration range c5 = 0.002 M to 0.4 M. The DNA molecular weights M were between 0.5 x 10(6) and 13 x 10(6). The relative change of intrinsic viscosity [eta] is linearly correlated to c5(-1/2) with a slope that increases with increasing M. This behaviour reflects the predominance of helix stiffening in chain expansion. At c5(112) > 0.01(-1/2 M-1/2 (Debye-Hückel screening radius 1/chi > (1/chi)*=3nm) the relative change of [eta] rises with a steeper slope. This effect increases with decreasing M suggesting that helix lengthening contributes to the chain expansion. Our model enables us to interpret other ionic-strength dependent effects known from literature. The start of the significant duplex elongation at (1/chi)* can be correlated to the polyion-charge arrangement. In accordance with our interpretation (1/chi)* is found to be greater for DNA-intercalator complexes.